Pengaruh Pendapatan Daerah terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Bali - Dimas Adijaya Nugraha; I Gusti Agung Ayu Apsari Anandari (Pusat Riset dan Inovasi Nasional, 2026)
Regional economic growth is a key indicator of development success aimed at improving public welfare. Bali Province generally demonstrates a positive trend in economic growth; however, it continues to experience disparities in growth among regencies and municipalities, where the Sarbagita area tends to grow more rapidly than other regions due to differences in economic structure and fiscal capacity. This condition indicates that the utilization of regional revenue sources has not been fully optimized to promote equitable economic growth. This study aims to analyze the effect of Regional Original Revenue (Pendapatan Asli Daerah/PAD), General Allocation Fund (Dana Alokasi Umum/DAU), and Special Allocation Fund (Dana Alokasi Khusus/DAK) on economic growth in regencies and municipalities in Bali Province during the period 2014–2024. The method employed is panel data regression analysis with a significance level of 5 percent. The results indicate that PAD, DAU, and DAK simultaneously have a significant effect on regional economic growth. Partially, PAD and DAU have a positive and significant effect on economic growth, while DAK does not show a significant effect, indicating that the utilization of DAK has not been optimal in stimulating regional economic activity. These findings emphasize the importance of strengthening fiscal independence through the optimization of PAD, more effective and productive management of DAU, and improvements in the planning and implementation of DAK to ensure a tangible contribution to sustainable and equitable economic growth in Bali Province.